Rail Transport Infrastructure on the Example of Level Crossing System - Tomasz, PerzyÅ„ski; Jerzy, Wojciechowski; Zbigniew, Åukasik (International Journal of Engineering and Technology, 2018)
The paper presents an analysis of the system of automatic level crossing. The proposed system belongs to a group of linear devices that ensure safe movement of motor vehicles at intersections of railway and car roads. In the paper, the computational tasks were carried out. On the basis of statistical data, the THR rate, which is characteristic for rail transport, was estimated. An example of modeling railway automation systems based on Markov processes is also presented. Â